#Vaccination: Identifying influencers in the vaccination discussion on twitter through social network visualisation - Jamali, Bujang Sanawi; Mus Chairil, Samani; Malia, Taibi (Universiti Malaysia Sarawak, 2017)
The emergence of social media such as Twitter has brought the discussion about vaccination to a new dimension. In this study, the researchers aim to explore the discussion on issues related to vaccination on social media platform, specifically Twitter and identify the ‘influencers’ in the conversation. The paper also highlighted some of the subgroups that exist within the network where the influential individuals or organisations are the centre of their attention. The findings show that there are six types of influencers that dictate the discourse on vaccination on Twitter which are: celebrity doctor, media organisations, homeopathy promoter, government and government agencies, blogger and renowned medical journal. It also found that some of the influencers have their own circle of audience while some of the influencers are sharing the same crowd. © 2017, Universiti Malaysia Sarawak. All rights reserved.